Motilitas, Viabilitas, dan Morfologi Spermatozoa Ayam Bangkok dengan Pengencer Dextrose dan Nacl Fisiologis 10% Pada Penyimpanan Suhu 5``C dan 26C - Kudratullah Kudratullah; Adji Santoso Sudrajat (Indonesian Journal of Applied Science and Technology, 2021)
This study aims to determine the effect of Dextros 10% diluent and physiological NaCl on the quality of Bangkok chicken spermatozoa on spermatozoa motility, viability and abnormality at 50C and 260C. The research method used a completely randomized design (CRD) with 4 treatments, each consisting of 7 replications. The materials used were 4 male Bangkok chickens aged ± 2 years, 1 female. The variables observed included motility, viability and morphology. The percentage of sperm motility in dextrose diluent 10% (62.1 ± 3.93%) showed a slight difference with the physiological NaCl diluent (62.9 ± 9.51%). The percentage of motility at 50C storage (62.1 ± 3.93%) was better than 260C (54.3 ± 3.45%). This indicated a significant difference (P <0.05) at the 5hour storage time. The percentage of viability showed that 10% dextrose (54.1 ± 5.57%) was better than physiological NaCl (52.21 ± 5.02%). The percentage of life Bangkok chicken sperm was higher at 50C storage (54.1 ± 5.57%) compared to 260C (39.8 ± 16.6%). The percentage of abnormalities with 10% dextrose diluent (8.07 ± 1.15%) was lower than that of NaCl diluent (10.0 ± 1.60%), and the percentage of abnormalities at 50C storage (8.07 ± 1.15) was lower than that of to 260C storage (10.79 ± 1.11%) and showed a significant difference (P <0.05) at 5 hours. In conclusion, the best of tender from this study was dextrose diluent 10% compared to physiological NaCl and storage at 50C was better than storage at 260C.